Effect of Ultrasound‐Guided Hydrorelease of the Multifidus Muscle on Acute Low Back Pain. (25th August 2020) - Kanamoto, Hirohito; Orita, Sumihisa; Inage, Kazuhide; Shiga, Yasuhiro; Abe, Koki; Eguchi, Yawara; Ohtori, Seiji
Abstract : Objectives: To examine improvement in acute low back pain (LBP) using ultrasound‐guided hydrorelease of the multifidus muscle. Methods: This prognostic cohort study was conducted in a private clinic on samples of 75 patients with acute LBP diagnosed based on physical and imaging findings. Hydrorelease of the multifidus muscle was performed at the L4/5 level. The LBP visual analog scale (VAS) scores (cm) before and 5 minutes after hydrorelease were statistically evaluated. We defined improvement rate (%) as {LBP VAS scores (cm) immediately before hydrorelease – LBP VAS scores (cm) 5 minutes after hydrorelease} × 100 / LBP VAS scores (cm) immediately before hydrorelease and examined the correlation of the Heckmatt score and average age with the improvement rate. Results: LBP VAS scores (cm) before and 5 minutes after hydrorelease were 7.19 ± 1.01 (mean ± SD) and 2.85 ± 1.25, respectively ( p  < 0.05). No significant correlations were noted between the LBP improvement rate and the Heckmatt score or age. There were no gender variations in the improvement rate. Conclusions: Ultrasound‐guided hydrorelease of the multifidus muscle led to considerable LBP VAS score improvement at the outpatient level. The improvement rate showed no correlations with the Heckmatt score or age, and there were no significant gender variations in the improvement rate. Therefore, fatty degeneration of muscles and change in muscle echogenicity due to age and gender may not be associated with muscular LBP. These findings suggest that multifidus muscle hydrorelease could be useful in the diagnosis and treatment of acute LBP.